Blockchain-based Framework for Supply Chain Management of Agri-food Sector in Malaysia - Chan, Kok Yong (Universiti Malaysia Sarawak (UNIMAS), 2020)
In the advent of blockchain technology, buzzword such as bitcoin, cryptocurrency and blockchain is gaining a lot of hypes around. As the enabler for cryptocurrency, the technology of blockchain is vastly applicable in different field, one of the most promising is supply chain. Recent research shows a lot interest on blockchain applying into supply chain, but most of them is covering the use case using public blockchain like Ethereum. Public blockchain is accessible for all user but feature like this might not be suitable for the use case of supply chain management as it involves unrelated party in the supply chain network. While some studies involve the implementation of blockchain based for supply chain solution, there is a gap on relating blockchain to supply chain transparency and traceability in quantitative approach. Quantitative approach is very meaningful in this study as it provides more clarity compared to qualitative approach in existing research. The first focus of this research is to investigate the differences between public and private blockchain. Secondly, this research proposed a framework to determine the transparency and traceability of each blockchain solution with the use case of supply chain of pepper industry in Malaysia. This study has presented results of traceability and transparency in a quantitative approach for both public blockchain, which is Hyperledger Fabric and Sawtooth. The result shows that Sawtooth able to achieve higher transparency and traceability than Fabric in most cases.